METHODOLOGICAL BASICS OF TRAINING FUTURE SCIENCE TEACHERS USING THE PRINCIPLES OF DIFFERENTIATION AND INDIVIDUALIZATION (Physical Culture and Sport: Scientific Perspective, 2024)
A successful solution to the problem of quality training of future teachers of natural sciences involves the activation of pedagogical efforts in a number of ways, the most important of which is the individualization and differentiation of education. The effectiveness of the training of future teachers of natural sciences using the principles of differentiation and individualization of education is related to the correct choice of the methodological foundations of this process, a specific set of methodological approaches, principles and laws. The purpose of the article is to analyze the methodological foundations of training future teachers of natural sciences using the principles of differentiation and individualization. To determine the theoretical foundations of the researched phenomenon, a set of interrelated research methods was used - analytical and comparative study and analysis of philosophical, psychological, pedagogical, scientific and methodological literature, regulatory legal documents, forecasting, generalization and conclusions. Research results. Methodological bases of training future teachers of natural sciences using the principles of differentiation and individualization define the key provisions of systemic, competence-based, practice-oriented and individual methodological approaches. The system approach makes it possible to consider the differentiated and individualized training of future teachers of natural sciences as a system from the standpoint of its structure, content, functions, set of methods, and system connections. A competent approach specifies the goal and final result of the training of future teachers of natural sciences. Practically oriented and individual methodological approaches make it possible to choose effective forms, methods, technologies and means of differentiated and individualized training of future teachers of natural sciences.
Keywords: methodology; scientific approaches; professional competence; differentiation and individualization of education; professional training; future teachers of natural sciences